2011
DOI: 10.1089/end.2010.0276
|View full text |Cite
|
Sign up to set email alerts
|

Third Prize: The Role of Endoscopic Nephron-Sparing Surgery in the Management of Upper Tract Urothelial Carcinoma

Abstract: NSS offered shorter hospital stay but had increased risk of recurrence. Therefore, extreme care should be made to rule out occult invasive tumors preoperatively. Patients being managed endoscopically must be informed of the necessity for close follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 47 publications
0
18
0
4
Order By: Relevance
“…Recently, the previously accepted standard of radical nephroureterectomy (RNU) for all stages of upper tract UC has been questioned. Nephron-sparing surgery (NSS) has been suggested as an alternative for patients with early stages of disease [22,23]. Reasons for NSS included marked differences in 5-year survival [23] and cancer-related mortality [24] between non-invasive and invasive UC of the UUT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the previously accepted standard of radical nephroureterectomy (RNU) for all stages of upper tract UC has been questioned. Nephron-sparing surgery (NSS) has been suggested as an alternative for patients with early stages of disease [22,23]. Reasons for NSS included marked differences in 5-year survival [23] and cancer-related mortality [24] between non-invasive and invasive UC of the UUT.…”
Section: Discussionmentioning
confidence: 99%
“…Nephron-sparing surgery (NSS) has been suggested as an alternative for patients with early stages of disease [22,23]. Reasons for NSS included marked differences in 5-year survival [23] and cancer-related mortality [24] between non-invasive and invasive UC of the UUT. Among 34 renal units managed endoscopically for low-grade UC of the UUT, cancer-specific and metastasis-free 5-year survival rates were 100% and 94%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, we selected the one with more areas and patients. After rounds of screening, twenty-three studies including 1587 KS and 3996 NU patients were enrolled meta-analysis at last (Hall et al, 1998;Shiraishi et al, 2003;Chen et al, 2005;Roupret et al, 2006;Giannarini et al, 2007;Lehmann et al, 2007;Lucas et al, 2008;Dragicevic et al, 2009;Gadzinski et al, 2010;Jeldres et al, 2010;Raymundo et al, 2011;Bin et al, 2012;Bing-bing et al, 2012;Colin et al, 2012;Grasso et al, 2012;Bagrodia et al, 2013;Cutress et al, 2013;Fajkovic et al, 2013;Klatte et al, 2013;Dalpiaz et al, 2014;Fukushima et al, 2014;Hoffman et al, 2014;Hung et al, 2014). All included studies were retrospective comparative study; no randomized controlled trials were identified.…”
Section: Literature Filtration and Quality Assessmentmentioning
confidence: 99%
“…Although the benefits of topical therapy are yet to be established, there is a strong body of evidence to support the endoscopic treatment of tumors, particularly those that are of low grade and small in size. Although recurrence rates may be higher and follow-up regimens much more strict, low-grade, low-volume disease uncommonly progresses in stage or grade and should be tackled endoscopically given the armamentarium currently at our disposal [6,31,32,[64][65][66]. Patients with high-grade disease fare poorly regardless of conservative treatment options, and nephroureterectomy should be advised [29,67,68].…”
Section: Expert Commentarymentioning
confidence: 99%